2020
DOI: 10.1038/s41598-020-61815-4
|View full text |Cite
|
Sign up to set email alerts
|

In-line filtration in very preterm neonates: a randomized controlled trial

Abstract: In-line filtration is increasingly used in critically-ill infants but its benefits, by preventing micro-particle infusion in very preterm neonates, remain to be demonstrated. We conducted a randomized controlled trial among very preterm infants allocated to receive either in-line filtration of all the intra-venous lines or standard care without filters. The primary outcome was differences greater than 20% in the median changes in pro-inflammatory cytokine serum concentrations measured at day 3 and day 8 (+/−1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Of those should be applied as a complimentary with the above main approaches were as follows: 1) standardisation of the concentration (Nemec, 2008), 2) optimisation of administration schedule (Maison et al, 2019) and 3) accurate pharmacist intervention. The standardisation of concentrations ensuring the preparation and administration of intravenous admixture was compatible (8). However, this finding should be further explored to confirm the compatibility of various combinations.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Of those should be applied as a complimentary with the above main approaches were as follows: 1) standardisation of the concentration (Nemec, 2008), 2) optimisation of administration schedule (Maison et al, 2019) and 3) accurate pharmacist intervention. The standardisation of concentrations ensuring the preparation and administration of intravenous admixture was compatible (8). However, this finding should be further explored to confirm the compatibility of various combinations.…”
Section: Resultsmentioning
confidence: 96%
“…Some studies showed a benefit, and others could not prove the significance of filter use. Two systematic reviews, one observational study, and one clinical trial have failed to prove the effectiveness of filters significantly in reducing complications, and also doubt the value of the filter (Foster et al, 2015;Niël-Weise et al, 2010;Tanaka et al, 2016;Virlouvet et al, 2020). However, some studies have been performed under ideal conditions, considered well-controlled and compliant to protocols so the incompatibilities were not identified.…”
Section: In-line Filtration For Trapping Precipitatesmentioning
confidence: 99%
“…Two German studies examined the use of lters in patients admitted to a pediatric intensive care unit (PICU), demonstrating the association between in-line ltration and a reduction in the incidence of SIRS (systemic in ammatory response syndrome) and serious complications (5,18). These results thought were not con rmed by a recent French study (19): they compared the pro le of pro-in ammatory cytokine levels when using lters or not in 146 very preterm infants and didn't found any signi cant change. The authors conclude that, despite this negative result, several bene ts provided by lters should be considered.…”
Section: Dissemination Plansmentioning
confidence: 59%
“…A French study addressing the blood concentration of cytokine in preterm infants with or without filter is currently in progress. 54…”
Section: Resultsmentioning
confidence: 99%